¿Es el EVA, realmente, un indicador del valor económico agregado? (2006)
In this article we analyze the relevance of EVA (Economic Value Added) as a tool for measuring value added, as well as its usefulness as an indicator in choosing investment projects. First, we show five ways of calculating EVA, providing examples of each case. Second, we show MVA (Market Value Added) and NPV (Net Present Value) to be equivalent as criteria used to evaluate investment projects. This is done with both the limited term and the perpetual cases, as well as for projects with partial and total recovery of the investment. We present a thorough analysis, showing the possibilities and limitations of EVA as a value added measure. We also introduce three measurements of residual income, CVA (Cash Value Added), Cash Flow Return on Investment (CFROI) and Economic Profit (EP), which complement EVA in the value measurement process. Finally, we introduce an example that explicitly shows the equivalence between CVA's present value, MVA and NPV.